Pemberian Analgetik Epidural Lumbal Kontinu sebagai Tatalaksana Nyeri Kanker dengan Metastasis - Mahmud; Kumala , Ratih; Alamsyah, Erry (Jurnal Komplikasi Anestesi, 2022)
Pain is the most common symptom of cancer patients. Pain in cancer patients is mainly caused by cancerprogressivity and tissue necrosis. Management of chronic pain needs considerable high socioeconomic costs. As an alternative for chronic pain management, a continuous infusion of local anesthetics via epidural catheter is recommended to alleviate chronic pain which caused by cancer pain in certain concentration that can relieve pain. We report 3 cases of patients with cancer pain related to metastatic process. All three patients had previously prescribed with oral opioids and fentanyl patches, which were inadequate in eliminating pain. In all these three patients, lumbal epidural catheter was placed and continuous local anesthetic drugs were administered in 1-2 ml/hour rate. The local anesthetics solution contains levobupivacaine 0.1%, morphine 0.08 mg/ml and klonidin 1.2 mg/ml.